Royleanone Derivatives From Plectranthus spp. as a Novel Class of P-Glycoprotein Inhibitors - Garcia, Catarina; Isca, Vera M. S.; Pereira, Filipe; Monteiro, Carlos M.; Ntungwe, Epole; Sousa, Francisco; Dinic, Jelena; Holmstedt, Suvi; Roberto, Amílcar; Díaz-Lanza, Ana; Reis, Catarina P.; Pesic, Milica; et al. (Frontiers in Pharmacology, 2020)
Cancer is among the leading causes of death worldwide. One of the most challenging obstacles in cancer treatment is multidrug resistance (MDR). Overexpression of P-glycoprotein (P-gp) is associated with MDR. The growing incidence of cancer and the development of MDR drive the search for novel and more effective anticancer drugs to overcome the MDR problem. Royleanones are natural bioactive compounds frequently found in Plectranthus spp. The cytotoxic diterpene 6,7-dehydroroyleanone (1) is the main component of the P. madagascariensis (Pers.) Benth. essential oil, while 7α-acetoxy-6β-hydroxyroyleanone (2) can be isolated from acetonic extracts of P. grandidentatus Gürke. The reactivity of the natural royleanones 1 and 2 was explored to obtain a small library of new P-gp inhibitors. Four new derivatives (6,7-dehydro-12-O-tert-butyl-carbonate-royleanone (20), 6,7-dehydro-12-O-methylroyleanone (21), 6,7-dehydro-12-O-benzoylroyleanone (22), and 7α-acetoxy-6β-hydroxy-12-O-benzoylroyleanone (23) were obtained as pure with overall modest to excellent yields (21-97%). P-gp inhibition potential of the derivatives 20-23 was evaluated in human non-small cell lung carcinoma NCI-H460 and its MDR counterpart NCI-H460/R with the P-gp overexpression, through MTT assay. Previously prepared diterpene 7α-acetoxy-6β-benzoyloxy-12-O-(4-chloro)benzoylroyleanone (4), has also been tested. The P-gp inhibiting effects of compounds 1 to 4 were also assessed through a Rhodamine 123 accumulation assay. Derivatives 4 and 23 have significant P-gp inhibitory potential. Regarding stability and P-gp inhibition potential, results suggest that the formation of benzoyl esters is a more convenient approach for future derivatives with enhanced effect on the cell viability decrease. Compound 4 presented higher anti-P-gp potential than the natural diterpenes 1, 2, and 3, with comparable inhibitory potential to Dexverapamil. Moreover, derivative 4 showed the ability to sensitize the resistant NCI-H460/R cells to doxorubicin.